Charge carrier trapping, recombination and transfer during TiO2 photocatalysis: An overview - Qian, Ruifeng; Zong, Huixin; Schneider, Jenny; Zhou, Guanda; Zhao, Ting; Li, Yongli; Yang, Jing; Bahnemann, Detlef W.; Pan, Jia Hong (Catalysis today, 2019)
[Display omitted] •Analytic methods to study the charge carrier dynamics are introduced.•The fates of charge carrier trapping and recombination are understood.•Various interfacial charge transfer processes are discussed case-by-case. Heterogeneous photocatalysis mediated by semiconducting TiO2 has attracted continuous interest during the past decades and has shown great potentials in environmental remediation and solar energy conversion. Basically, photocatalysis is initiated by the TiO2 excitation. The generated charge carriers undergo trapping, recombination, and interfacial transfer before proceeding the redox reaction at TiO2 surface. Monitoring the charge carrier dynamics is of particulate importance for understanding the underlying mechanism and designing efficient photocatalysts. This review overviews the recent progress in characterization of charge carrier dynamics. We will present the analytic techniques for monitoring the fate of charge carriers at each elementary photocatalytic step, including charge carrier generation, trapping and recombination inside the photocatalyst, as well as the interfacial charge transfer. The charge carrier dynamics at TiO2/H2O interface, hole transfer reactions for O2 production, and photocatalytic oxidation of organic compounds and nitric oxides, and electron transfer reactions for photocatalytic reduction of viologens and metal ions are addressed, aiming at a deeper understanding of photocatalytic process.